A comparison of dance interventions in people with Parkinson disease and older adults. Issue 1 (May 2015) - McNeely, M.E.; Duncan, R.P.; Earhart, G.M.
Highlights We review the effects of dance on motor function in older adults and people with PD. Knowledge gaps, limitations, and opportunities for further study are identified. Fewer dance styles and fewer aspects of motor function have been studied in PD. Overall, dance provides wide-ranging motor benefits in both populations.